1998
DOI: 10.1016/s0266-7681(98)80085-5
|View full text |Cite
|
Sign up to set email alerts
|

The Histopathology of De Quervain’s Disease

Abstract: The histopathological appearances of the tendon sheath and synovium from 23 patients treated surgically for de Quervain's disease are described and compared with 24 controls. The condition was not characterized by inflammation, but by thickening of the tendon sheath and most notably by the accumulation of mucopolysaccharide, an indicator of myxoid degeneration. These changes are pathognomonic of the condition and are not seen in control tendon sheaths. The term 'stenosing tenovaginitis' is a misnomer and we be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
87
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(93 citation statements)
references
References 9 publications
1
87
0
5
Order By: Relevance
“…Similarly, Nakamichi et al reported that the ligament and tenosynovium histology was normal in most cases of idiopathic carpal tunnel syndrome and typical histological changes were not encountered related to idiopathic carpal tunnel syndrome [29]. In another histopathological study related to De Quervain disease, it was suggested that intrinsic degenerative mechanisms played a role in the disease pathogenesis rather than inflammatory events [30]. The histopathological results of the current study show a similarity to these examples given of histopathological studies of carpal tunnel syndrome and De Quervain disease.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Nakamichi et al reported that the ligament and tenosynovium histology was normal in most cases of idiopathic carpal tunnel syndrome and typical histological changes were not encountered related to idiopathic carpal tunnel syndrome [29]. In another histopathological study related to De Quervain disease, it was suggested that intrinsic degenerative mechanisms played a role in the disease pathogenesis rather than inflammatory events [30]. The histopathological results of the current study show a similarity to these examples given of histopathological studies of carpal tunnel syndrome and De Quervain disease.…”
Section: Discussionmentioning
confidence: 97%
“…A tenossinovite estenosante de De Quervain caracterizase por ser a inflamação da bainha do abdutor longo e extensor curto do polegar, no primeiro compartimento dorsal do punho, acometendo mais frequentemente as mulheres na faixa etária entre 30 e 50 anos [3][4][5][6][7][8] . Essa doença está associada principalmente a sobrecarga das atividades diárias das mãos e punho, trauma crônico secundário, podendo também ser causada por outros fatores, mas em muitos casos não há uma causa bem definida.…”
Section: Discussionunclassified
“…Despite the name Tenosynovitis the histopathological feature of this disorder is not inflammation, but is deposition of mucopolysaachride, myxoid degeneration and neovascularisation as seen in different fibrous metaplasia. 1,2,3 . The condition is caused by impaired and repetitive gliding of the tendons, microtrauma due to overuse of the first dorsal compartment tendons (Abductor pollicis longus and extensor pollicis brevis).in long standing cases of de Quervains tenosynovitis thickening of extensor retinaculum can be seen.…”
Section: Introductionmentioning
confidence: 99%